Quick segmentation for complex curved surface with local geometric feature based on IGES and Open CASCADE. (September 2015) - Wang, Fu-ji; Ma, Jian-wei; Xu, Qiang; Jia, Zhen-yuan; Yang, Yan-yu
Highlights: A segmentation system for efficient machining of complex curved surface is proposed. Feature size of a surface patch is defined by its boundary information. Surface patches with different feature sizes will be processed by different parameters. Experiment shows efficiency is increased by 28.18%. Estimations of other models predict efficiency can be increased by 20.14% and 12.33%. Abstract: Complex curved surface parts with local geometric feature are usually critical parts in high-end equipments. However, the processing for this kind of parts is usually difficult or inefficient due to the adoption of difficult-to-machine material and special structure. Current approaches cannot satisfy the rapid development of high-end equipments. Due to the existence of the local geometric feature for the parts, processing such parts with constant machining parameters is less applicative, restricting the improvement of machining efficiency. By separating the local geometric feature and generating tool path for the local geometric feature and the remaining processing area separately, the more efficient machining with variable machining parameters will be obtained for the complex curved surface with local geometric feature. In this way, the quick segmentation for the complex curved surface with local geometric feature is of great importance to the NC machining with variable machining parameters for this kind of parts, and a quick segmentation system is developed based on Initial Graphics Exchange Specification (IGES) and Open CASCADE (OCC) platform in this study. The complex curved surface model in IGES format is firstly imported into the system and then trimmed into independent surface patches. After computing the feature size of each surface patch, the segmentation for the complex curved surface is achieved by sorting and classifying the surface patches according to their feature sizes. Taking the whole impeller with small splitter blades for an example, the experimental result shows that the segmentation of small splitter blades from the whole impeller is successful and a serialized processing program could be generated, and then the whole impeller could be machined precisely and efficiently with NC equipment. In the machining experiment, it is proved that the machining with various machining parameters can improve the efficiency by 28.18% in the comparison experiment, 20.14% and 12.33% in the estimation. The research provides an important foundation for the high quality and more efficient machining of the complex curved surface with local geometric feature.